A A COMPARATIVE STUDY OF QUALITY CONTROL TESTING ON CANDESARTAN CILEXETIL CONVENTIONAL TABLETS IN IRAQ - ALBO HAMRAH, KARRAR TALIB KHUDHAIR; AL-SHAIBANI, ABULFADHEL JABER NEAMAH; AL-EDRESI, SARMAD SABAH; AL-GBURI, KARRAR MOHAMMED HASAN (International Journal of Applied Pharmaceutics, 2020)
Objective: The present study was performed to compare the quality of conventional tablets loaded with candesartan cilexetil. The selected candesartan cilexetil tablets were commercialized in the Iraq market and produced by different companies. Methods: Different batches of candesartan cilexetil oral tablets (the concentration of candesartan was 8 mg) were subjected to quality control tests. Tests included weight variation, friability, hardness, drug content, disintegration time and in vitro release study. The protocols of these tests were performed according to USP pharmacopeia. Results: The results, in this study, revealed that all the used batches of candesartan cilexetil oral tablets complied with the specification of USP pharmacopeia for weight uniformity, friability value (% loss) was<1. Hardness results of the tablets were 4.9-6.6 Kg/cm2, which was within the required limits (i.e. 4-8 Kg/cm2). Disintegration time was<15 min in both Simulated Gastric Fluid (SGF) and Simulated Intestinal Fluid (SIF). The percentage of drug content in all marketed tablets was found between 96.2 % and 99.8 %, reflecting compliance with the pharmacopeia limits (i.e. 85-115 %). An in vitro release study indicated that the release of all marketed tablets exceeds 80 % within 15 min. Conclusion: All the studied tablets, loaded with candesartan cilexetil, were produced within the standard criteria of tablet production. The quality control analysis of the selected tablets, in this study, revealed satisfactory pharmaceutical properties (including safety and effectiveness) that comply within the limits of USP pharmacopeia.